Peran Inklusi Keuangan dalam Mengatasi Ketimpangan Pendapatan di Indonesia - Rifky Sahran; Muhammad Yusri Zamhuri; Anas Iswanto Anwar (Al-Buhuts, 2024)
This study aimed to analyze the impact of financial inclusion and other macroeconomic variables on income inequality across 33 provinces in Indonesia from 2020 to 2023. The analytical methods employed included descriptive analysis and panel data regression. The results of the descriptive analysis indicated that income inequality in Indonesia fell within the moderate category, while financial inclusion showed a year-on-year increase, although it remained at a medium level of inclusiveness. At a significance level of 5%, the regression results revealed that financial inclusion had a negative but insignificant effect on income inequality. The macroeconomic variables that significantly influenced income inequality were inflation, which had a positive effect, and the real Provincial Minimum Wage (UMP), which had a negative effect, while economic growth had a positive but insignificant impact